2019
DOI: 10.1186/s12875-019-1052-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in primary care provider utilization by phase of care for women diagnosed with breast cancer: a CanIMPACT longitudinal cohort study

Abstract: BackgroundPrimary care providers (PCPs) have always played an important role in cancer diagnosis. There is increasing awareness of the importance of their role during treatment and survivorship. We examined changes in PCP utilization from pre-diagnosis to survival for women diagnosed with breast cancer, factors associated with being a high user of primary care, and variation across four Canadian provinces.MethodsThe cohorts included women 18+ years of age diagnosed with stage I-III invasive breast cancer in ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
3
0
1
Order By: Relevance
“…Our study evaluated the effect of physical comorbidity and MHH on the change in PCP visit rates during breast cancer treatment. Similar to previous studies, [7][8][9] in this population-based cohort of women in Ontario with breast cancer, we found that the absolute number of PCP visits over 6 months increased from 2.3 at baseline to 3.4 during adjuvant chemotherapy. In our adjusted analyses, we found that although women with high physical comorbidity levels and MHH had more visits during the baseline and treatment periods, the increase in PCP visits from baseline to treatment periods was smaller than in those with low physical comorbidity levels and no MHH.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study evaluated the effect of physical comorbidity and MHH on the change in PCP visit rates during breast cancer treatment. Similar to previous studies, [7][8][9] in this population-based cohort of women in Ontario with breast cancer, we found that the absolute number of PCP visits over 6 months increased from 2.3 at baseline to 3.4 during adjuvant chemotherapy. In our adjusted analyses, we found that although women with high physical comorbidity levels and MHH had more visits during the baseline and treatment periods, the increase in PCP visits from baseline to treatment periods was smaller than in those with low physical comorbidity levels and no MHH.…”
Section: Discussionsupporting
confidence: 89%
“…6 Despite the lack of a clear role for PCPs during breast cancer treatment, patients with breast cancer have been shown to visit their PCPs more often when they are receiving adjuvant chemotherapy than before their breast cancer diagnosis. [7][8][9] The reasons for this remain unclear. Previous qualitative work with providers suggests that PCPs' main roles in caring for patients with cancer are not to manage urgent issues during chemotherapy, but rather to coordinate care, manage comorbidities and provide psychosocial care.…”
mentioning
confidence: 99%
“…During interviews with patients, participants shared that their PCPs were involved in providing care primarily while they were undergoing diagnostic investigations and then after they completed treatment and were transferred from the cancer centre. However, results from administrative health data studies in four Canadian provinces show that patients with breast cancer were seen more often by PCPs during the treatment phase than pre-diagnosis, and were more likely to be high users of primary care with a greater number of comorbidities [ 17 ]. Perhaps the participants in this study were less complex patients with fewer comorbid conditions and as such, did not require extensive PCP involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The overall goal of this program of research was to examine and address gaps in care coordination between oncology and primary care. After conducting several studies to identify gaps in cancer care coordination [ 3 , 7 , 14 , 15 , 16 , 17 ], the team organized a consultative workshop with stakeholders (patients, caregivers, PCPs, cancer specialists and health system administrators) to obtain recommendations for developing an intervention. Stakeholders recommended implementing a web-based communication system for asynchronous direct communication between PCPs and cancer specialists [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estudios sobre la calidad de vida del enfermo oncológico indican como la pérdida de funcionalidad y los cambios en las actividades diarias se relacionan con la aparición de alteraciones emocionales, mayor sintomatología y deterioro en la calidad de vida (1)(2)(3)(4)(5)(6) . Los problemas que ha de afrontar el paciente oncológico se asocian con las dificultades derivadas de la enfermedad y el tratamiento (síntomas, efectos secundarios, etc.).…”
Section: Introductionunclassified